(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
The aim of the work was evaluate the effects of testosterone undecanoate (TU) treatment combined with moderate physical training on: the estrous cycle, body weight (BW), motor behavior (MB), and the morphohistology of the reproductive system, the liver and kidney in rats. Female Wistar rats (180 g - 250 g) were divided as follows: sedentary + TU (S + TU), trained + TU (T + TU), sedentary + vehicle (S + V), trained + vehicle (T + V). The rats swam 50 min/Day, strapped with a 5% BW load, for 4 weeks. During this training, (BW) was monitored daily as well as the estrous cycle (EC) by vaginal smear. The TU (15 mg/kg s.c) was administered 3 times/week for 4 weeks. At the end of the study, data on MB, BW and morphohistopathological changes in viscera were compiled. The (T + TU) group had on average, a higher (BW) in the fourth week compared to the first week, and (BW) higher than (S + V) and (S + TU) groups. We noted an interruption in the EC and a decrease in weight of ovaries in animals treated with TU. In addition, there was an increase in the relative weight of the heart in groups (T + V) and (T+ TU), and kidneys in group (T + TU). Histopathological analysis showed periportal congestion and isolated foci of hepatic necrosis in rats with TU. Thus, TU combined with training abolished the EC, promoted ovarian atrophy, liver necrosis, cardiac hypertrophy and a decrease in motor activity.